Peningkatan Pemahaman Haid melalui Kajian Fiqih Wanita di Desa Barong Sawahan - Khotim Fadhli; Azizah Azhari; Muhamad Hamim Thohari; Kholis Firmasyah (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2021)
Society in general tends to refer more to the understanding of the previous society. It can be seen from their daily lives that they are not too updated with the times. Like in the field of fiqh, people tend to be indifferent to the development of fiqh. So that when people who do have a good understanding of religion will have different opinions. The public will be complacent about the opinions of the previous community and will not use the opinions of people who are experts and understand the development of fiqh. For this reason, as a person who understands fiqh better, it is necessary to convey it in a good method without offending people's understanding. In addition, it is also necessary to adjust to the development of the times. For that it is necessary to convey understanding and also adapt it to the times. For this reason this study is an option because it can adjust to the times without forgetting its original purpose, which is to provide an updated understanding of fiqh. And with the implementation of the study of women's fiqh, it can gradually change the way society views it. Many positive responses were received even though the target was still for the elderly. However, with a good response, it can make the work program run will have an influence in the community. And when the parents have gone well, all that needs to be done is to package this women's fiqh study activity more fresh among teenagers. Keywords: Fiqh Understanding; Sosial Culture.